Adolescent Finswimmers: Early Myocardial Adaptations in Different Swimming Styles - Vasileios Stavrou; Konstantinos Tsarouhas; Eleni Karetsi; Panagiotis Michos; Zoe Daniil; Konstantinos I. Gourgoulianis (MDPI AG, 2018)
Background: The purpose of our study was to investigate early differences in the adolescent female finswimmers’ echocardiography parameters, possibly associated with different swimming-style training and different training equipment (monofin (MF) versus bifin (BF)). Method: Forty-three female finswimmers participated in our study (age: 15.6 ± 2.1 years, body mass index: 20.4 ± 2.2 kg/m2, body surface area: 1.56 ± 0.04 m2, body fat: 11.2 ± 0.6%) and were divided into two groups, according to the swimming style practiced (MF vs BF). Anthropometric characteristics, echocardiography and arterial pressure were measured. The independent t-test was used for statistical comparisons between groups. Stepwise multivariate regression analysis was applied to investigate associations between various variables. Results: The two groups used training equipment with different weights (p < 0.001). Female adolescent finswimmers presented signs of myocardial hypertrophy depicted by the increased left ventricle myocardial mass indexed to body surface area (101.34 ± 23.65). Different patterns of myocardial hypertrophy were observed for the two groups; MF swimmers presented concentric hypertrophy, while BF swimmers presented eccentric hypertrophy (relative wall thickness MF = 0.46 ± 0.08 vs BF = 0.39 ± 0.06 cm, p < 0.05). MF swimmers had also higher left ventricular posterior wall diameters (p < 0.05), lower stroke volume values (p < 0.05) and lower ejection fraction (p < 0.05) compared to BF athletes. Conclusion: Adolescent female finswimmers presented different patterns of myocardial hypertrophy possibly related to different training protocols and modes of exercise.